Analisis Kesiapan Sekolah Dengan Melakukan Tindak Lanjut Dalam Pelaksanaan Asesment Nasional: Analysis of School Readiness Through Follow-Up Actions in the Implementation of the National Assessment - Zulfa Afifah; Fitri Hilmiyati; Fithri Meiliawati (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The background of this study is the lack of school readiness in implementing the Computer-Based National Assessment (ANBK) and the weak computer operation skills of students at SDS IT Subulussalam, Kresek, Tangerang, Banten. This study employed a qualitative research method, in which the researcher described the findings based on field conditions. The key research instrument was the researcher themself, with data collection techniques including observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results of this study can be summarized as follows: (1) The planning of ANBK activities at SDS IT Subulussalam Kresek was the responsibility of the school principal, who ensured that all necessary facilities and infrastructure were adequately prepared, especially the laptops used during the ANBK. (2) The implementation of ANBK at SDS IT Subulussalam was conducted in the teachers’ office due to the availability of an internet connection, and the ANBK was carried out in two sessions. (3) The evaluation of ANBK activities at SDS IT Subulussalam Kresek involved the school conducting socialization programs for parents, teachers, and students, as well as coordinating with various institutions to prepare the requirements. (4) The follow-up to ANBK activities at SDS IT Subulussalam Kresek focused on improving learning services for students at both lower and upper grade levels, with an orientation toward literacy and numeracy development.